2013
DOI: 10.3892/mmr.2013.1585
|View full text |Cite
|
Sign up to set email alerts
|

Houttuynia cordata Thunb inhibits the production of pro-inflammatory cytokines through inhibition of the NFκB signaling pathway in HMC-1 human mast cells

Abstract: Houttuynia cordata Thunb (HCT) is widely used in oriental medicine as a remedy for inflammation. However, at present there is no explanation for the mechanism by which HCT affects the production of inflammatory cytokines. The current study aimed to determine the effect of an essence extracted from HCT on mast cell-mediated inflammatory responses. Inflammatory cytokine production induced by phorbol myristate acetate (PMA) plus a calcium ionophore, A23187, was measured in the human mast cell line, HMC-1, incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…HC is used as a folk therapy against influenza, asthma, allergy, cancer (Yang and Jiang, 2009), and also had the anti-inflammatory activity (Lee et al, 2013). In China, the traditional medicines are mostly prepared in a form of apozem.…”
Section: Discussionmentioning
confidence: 99%
“…HC is used as a folk therapy against influenza, asthma, allergy, cancer (Yang and Jiang, 2009), and also had the anti-inflammatory activity (Lee et al, 2013). In China, the traditional medicines are mostly prepared in a form of apozem.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of synovial fibroblasts leads to the development of RA and initiates joint destruction in the long term (3)(4)(5). Previous studies have demonstrated that TNF-α, interleukin (IL)-6 and IL-8 are important proinflammatory cytokines in the pathogenesis of RA (21)(22)(23)(24), and that the inhibition of TNF-α and IL-6 is effective in the treatment of patients with RA (25)(26)(27). Notably, several studies have indicated that HCT was able to efficiently inhibit IL-6, IL-8 and TNF-α (24,28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TNF-α, interleukin (IL)-6 and IL-8 are important proinflammatory cytokines in the pathogenesis of RA (21)(22)(23)(24), and that the inhibition of TNF-α and IL-6 is effective in the treatment of patients with RA (25)(26)(27). Notably, several studies have indicated that HCT was able to efficiently inhibit IL-6, IL-8 and TNF-α (24,28). In addition, nonsteroidal anti-inflammatory drugs (NSAIDs) have been demonstrated to be efficacious in the treatment of RA by binding to cyclooxygenase (COX) enzymes and therefore inhibiting the production of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be useful for reducing the symptoms associated with rheumatoid arthritis (RA), without the marked gastrointestinal side-effects of NSAIDs. Studies have also indicated that HCT is able to efficiently inhibit IL-6, IL-8 and TNF-α production (27,28).…”
Section: Other Anti-inflammatory Activitymentioning
confidence: 99%